Implementation of STEM E-Module with SDGs Principle to Improve Science Literacy and Environment-friendly Attitudes in Terms of Gender - Prima Aswirna; Vira Kiswanda; Nurhasnah Nurhasnah; Reza Fahmi (Jurnal Tadris Kimiya, 2022)
Scientific literacy plays an important role in developing education in the 21st century. However, the current student’s scientific literacy ability is relatively low. The millennial generation has been named as a generation that has an environment-friendly attitude. In cases that occur in the field, many students still litter and are not friendly to the environment. There are no teaching materials that develop scientific literacy and environment-friendly attitudes in implementing STEM (Science, Technology, Engineering, and Mathematics) with the principles of Sustainable Development Goals (SDGs). This research aims to produce a STEM e-module with the principles of SDGs to improve scientific literacy and environment-friendly attitudes of 11th grade students regarding gender that is valid, practical, and effective. This research is development research (R&D) with the Plomp model. The data analysis results show that the STEM e-module with SDGs principle has a good impact on students' scientific literacy skills and environment-friendly attitudes. The developed e-module can also help students practice scientific literacy and improve a better environment-friendly attitude.